Capturing microbial sources distributed in a mixed-use watershed within an integrated environmental modeling workflow. (January 2018) - Whelan, Gene; Kim, Keewook; Parmar, Rajbir; Laniak, Gerard F.; Wolfe, Kurt; Galvin, Michael; Molina, Marirosa; Pachepsky, Yakov A.; Duda, Paul; Zepp, Richard; Prieto, Lourdes; Kinzelman, Julie L.; et al.
Abstract: Many watershed models simulate overland and instream microbial fate and transport, but few provide loading rates on land surfaces and point sources to the waterbody network. This paper describes the underlying equations for microbial loading rates associated with 1) land-applied manure on undeveloped areas from domestic animals; 2) direct shedding (excretion) on undeveloped lands by domestic animals and wildlife; 3) urban or engineered areas; and 4) point sources that directly discharge to streams from septic systems and shedding by domestic animals. A microbial source module, which houses these formulations, is part of a workflow containing multiple models and databases that form a loosely configured modeling infrastructure which supports watershed-scale microbial source-to-receptor modeling by focusing on animal- and human-impacted catchments. A hypothetical application – accessing, retrieving, and using real-world data – demonstrates how the infrastructure can automate many of the manual steps associated with a standard watershed assessment, culminating in calibrated flow and microbial densities at the watershed's pour point. Highlights: Describes mathematical formulations of the Microbial Source Module. Determines microbial loading rates associated with land-applied manure on undeveloped areas from domestic animals. Determines microbial loading rates associated with direct shedding on undeveloped lands by domestic animals and wildlife. Determines microbial loading rates associated with urban or engineered areas. Determines microbial loading rates associated with direct discharge to streams from septics and domestic animals shedding. Supports watershed-scale microbial source-to-receptor modeling by focusing on animal- and human-impacted catchments. Links to a user interface that automates data collection, collation of microbial sources, and watershed delineation. Links to a user interface that automates flow and microbial calibration at downstream receptors.